(untitled) (Acta Scientiarum. Biological Sciences, 2013)
Heterorhabditis sp SL0708 (Rhabditida: Heterorhabditidae) is a native entomopathogenic nematode from Alcalá, Valle del Cauca (Colombia), a natural enemy of insects that can be used for controlling Plutella xylostella L, Conotrachelus psidii Marshall and Delia platura (Meigen); however its biological characterization is unknown. In order to know about the infective capacity of the isolate, tests were made with last instar larvae of Galleria mellonella (Lepidoptera: Pyrallidae) on penetration, one by one, exposure time, dose response and foraging strategy. The average infecting juveniles (IJ) entering larvae was 3 (1.5%). In the one-on-one test, larvae mortality ranged between 8.3 and 16.7%. There was no significant difference (p < 0.05) between treatments and in number of dead larvae in the exposure time and dose response assays. Heterorhabditis sp. SL0708 presented a cruiser foraging strategy, which indicates that it can be used for sessile or cryptic hosts.